PENYUSUNAN BOOKLET SCAFFOLDING MENGGUNAKAN TEORI POLYA MATERI TRIGONOMETRI - Nuriska Indriantie; Mohamad Rif'at; Dede Suratman (Jurnal AlphaEuclidEdu, 2022)
This research aims to compile a scaffolding booklet using Polya's theory of trigonometric subject. The method of this research is a research and development (R&D) method with a 4-D development model. The research subject are the student of class X MIA 1 SMAN 6 Pontianak. Data collection tools used are unstructured interviews and questionnaires. Data analysis is viewed from the results of the questionnaire assessment, how to develop booklets and booklets. From this research, it was found that the clarity of how to solve trigonometric problems in textbooks used in schools is still not clear, because the completeness of the fourth polya step, namely at the stage of re-examining, does not exist and there are still students who do not understand how to solve the problems given. The preparation of this booklet is to improve and clarify how to solve the problems in the book. The completeness of the polya steps that did not exist before came into existence and the stages of solving Polya's problems become complete in the booklet. Students who do not understand the explanations in the textbooks will at least understand enough when given an explanation of how to solve problems in the booklet.